2011
DOI: 10.1107/s1600536811029679
|View full text |Cite
|
Sign up to set email alerts
|

(1E,1′E)-4,4′-[1,1′-(Hydrazine-1,2-diylidene)bis(ethan-1-yl-1-ylidene)]diphenol dihydrate

Abstract: Key indicators: single-crystal X-ray study; T = 100 K; mean (C-C) = 0.002 Å; R factor = 0.046; wR factor = 0.125; data-to-parameter ratio = 21.1.The asymmetric unit of the title compound, C 16 H 16 N 2 O 2 Á-2H 2 O, contains one half-molecule of diphenol and one water molecule. The complete diphenol molecule is generated by a crystallographic inversion centre. In the molecule, the central C methyl -C N-N C-C methyl plane makes a dihedral angle of 8.88 (6) with its adjacent benzene ring. In the crystal, the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The methyl groups are twisted from the planes of benzene (C1-C6 and C1A-C6A) rings and their orientations can be indicated by the torsion angles (C1-C6-C7-C8 and C1A-C6A-C7A-C8A) = 24.91 (19)°. The bond length are within the normal range (Allen et al, 1987) and are comparable with the related structures (Chantrapromma et al, 2011;Fun, Nilwanna et al, 2011;Jansrisewangwong et al, 2010;Nilwanna et al, 2011). In the crystal structure ( Fig.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…The methyl groups are twisted from the planes of benzene (C1-C6 and C1A-C6A) rings and their orientations can be indicated by the torsion angles (C1-C6-C7-C8 and C1A-C6A-C7A-C8A) = 24.91 (19)°. The bond length are within the normal range (Allen et al, 1987) and are comparable with the related structures (Chantrapromma et al, 2011;Fun, Nilwanna et al, 2011;Jansrisewangwong et al, 2010;Nilwanna et al, 2011). In the crystal structure ( Fig.…”
Section: Methodssupporting
confidence: 86%
“…Owing to our medicinal chemistry research on hydrazones, we previously reported the synthesis and crystal structures of some hydrazone derivatives (Chantrapromma et al, 2011;Fun, Nilwanna et al, 2011;Jansrisewangwong et al, 2010;Nilwanna et al, 2011). The title compound was synthesized to study for antibacterial activity and fluorescence properties in order to get more detail on the structural activity relationship through comparing with other closely related compounds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Searches of the Cambridge Structural Database (CSD Version 5.41, March 2020 update; Groom et al, 2016) were carried out to identify structures with geometrically similar OÁ Á ÁO hydrogen-bonding motifs and similar distorted T-shaped C-HÁ Á Á motifs. Square rings comprised of two alcohol O-H groups and two water molecules are comparatively uncommon in organic crystals; examples include CSD refcodes KONTIQ (Demirtaş et al, 2011), AYOPIO (Chantrapromma et al, 2011), CERYIK (Zhang et al, 2018) and VABKOA (Li et al, 2010). However, the compound most closely related structurally to phenol hemihydrate that contains this motif is TMBUOL (2,3,3trimethyl butan-2-ol hemihydrate; Pachler & von Stackelberg, 1963).…”
Section: Database Surveymentioning
confidence: 99%